Safety and effectiveness of HSK21542 for hemodialysis patients: a multiple ascending dose study - Pan, Mingming; Wang, Guihua; Zhou, Li; Xu, Yan; Yao, Li; Wu, Chaoqing; Mei, Changlin; Zhao, Zhanzheng; Sun, Dong; Guan, Tianjun; Chen, Qinkai; Shi, Ming; et al. (Frontiers in Pharmacology, 2023)
Background: HSK21542, a novel selective peripherally-restricted κ-opioid receptor agonist has been proven to be a safe and effective analgesic and antipruritic drug in both in vitro and in vivo studies. We aimed to evaluate its safety, pharmacokinetics and efficacy in hemodialysis patients over a 1-week treatment period, and to establish the optimal dosage for a further 12-week stage 2 trial. Methods: In this multiple ascending dose study, hemodialysis patients were randomly assigned to receive HSK21542 (0.05-0.80 μg/kg), or a placebo three times within 2.5 h at the end of each dialysis session for 1 week. Safety evaluations included reports of treatment-emergent adverse events (TEAEs); pharmacokinetics and efficacy outcomes were also assessed. Results: Among the 44 screened patients, 41 were enrolled and completed the trial. The overall incidence of TEAEs was higher in the HSK21542 group compared to the placebo group, with an incidence of 75.0, 50.0%, 75.0% and 88.9% in the range of 0.05–0.80 μg/kg. All TEAEs were grade 1 or 2 in severity. HSK21542 exhibited linear pharmacokinetics characteristics within the dose range 0.05–0.80 μg/kg, without drug accumulation after multiple-doses. Compared to the placebo, a significant decrease of the weekly mean Worst Itching Intensity Numerical Rating Scale was found in the HSK21542-0.30 μg/kg group (P = 0.046), but without significant improvement in the Skindex-16 score. Conclusion: HSK21542 was well tolerated in the dose range 0.05–0.80 μg/kg in hemodialysis patients. HSK21542-0.3 μg/kg exhibited promising efficacy in patients with moderate to severe pruritus and warrants a further Stage 2 trial.